Peran Suami Isteri Katolik Dalam Membangun Komunikasi Yang Efektif Di Stasi St. Petrus Kolilanang Paroki St. Petrus Kolisagu - Sili, Pricila Devi P.; Lelu, Skolastika; Aran, Alfonsus Mudi (Jurnal Pendidikan Indonesia, 2025)
The purpose of this study is to find out the role of Catholic husband and wife in domestic welfare and to analyze the causative factors of the role of Catholic husband and wife in household welfare at St. John's Station. Peter was stunned. The role of husband and wife in marriage is very important to understand. Each couple has different responsibilities, such as taking care of the house, supporting each other emotionally, and managing finances. Human life in this day and age experiences various challenges related to customary, economic, and faith factors that affect family welfare. The method used in this study is a qualitative descriptive method, using data collection techniques in the form of observation, interviews, and documentation. The research was carried out from February to May 2025. The results of this study found that there was no openness between married couples. There are couples who argue that, in order to avoid ongoing conflict, effective communication is needed, so that the couple is more open to what they feel about the truth from their own point of view, approval and support.